THE INFLUENCE OF CAPITAL LOANS AND WOMEN'S SAVINGS AND LOAN DEVELOPMENT ON THE DEVELOPMENT OF MICRO SMALL AND MEDIUM ENTERPRISES - Rosanti, Rosanti; Midesia, Shelly (IAIN Lhokseumawe, 2023)
The purpose of this study was to determine the effect of capital loans and women's savings and loan guidance on the development of MSMEs in Meloak Sepakat Village, Gayo Lues Regency. This study uses primary data sourced from a research questionnaire with a sample of 120 respondents. Methods of data analysis using multiple linear regression equations, t test, F test and the coefficient of determination (R2). The results showed that capital loans and women's savings and loan coaching have an effect on the development of MSMEs in Meloak Sepakat Village, Gayo Lues Regency, which is known from the multiple linear regression equation Y = 4.281 + 0.299X1 + 0.692X2. The t test results show that capital loans have a significant effect on the development of MSMEs in Meloak Sepakat Village, Gayo Lues Regency. The development of savings and loans for women has a significant effect on the development of MSMEs in Meloak Sepakat Village, Gayo Lues Regency. Then the results of the F test, simultaneously capital loans and women's savings and loan guidance have a significant effect on the development of MSMEs in Meloak Sepakat Village, Gayo Lues Regency.